Responding to conflict: Does “Cash Plus” work for preventing malnutrition? New evidence from an impact evaluation of Yemen’s Cash for Nutrition Program - Kurdi, Sikandra; Breisinger, Clemens; Ibrahim, Hosam; Ghorpade, Yashodhan; Al-Ahmadi, Afrah (International Food Policy Research Institute, 2019)
An impact evaluation of Yemen’s Cash for Nutrition program provides new evidence of the benefits of “cash plus” transfer programs to meet nutritional needs in conflict situations. Conflict has become a major driver of humanitarian crises globally, requiring responses that not only meet people’s immediate need for calories, but also ensure that aid recipients, especially children and pregnant women, receive adequate diet to avoid long-term impacts of malnutrition. The program in Yemen combined cash transfers with nutritional education using soft conditionality, with significant positive impacts on maternal and child dietary diversity, children’s height and weight measures, and the likelihood of children being diagnosed with moderate or severe acute malnutrition.